Hubungan Pengetahuan dengan Perilaku Sedentari yang Berisiko Obesitas pada Remaja di Kota Medan - Pika Asyera br Sinulingga; Lita Sri Andayani; Zulhaida Lubis (Jurnal Health Sains, 2021)
Sedentary behavior is called sedentary physical activity or physical inactivity. At this time, teenagers are adopting a lot of temporary behavior, especially when the COVID-19 pandemic is currently happening, thus limiting the activities and activities of teenagers. Sedentary behavior can put you at risk of obesity. This study aims to see the relationship between adolescent knowledge and sedentary behavior. This type of research is a quantitative study using a cross sectional design. The number of respondents in this study consisted of 267 people. Data obtained through the results of questionnaires which were conducted online using google form. The results showed that 192 adolescents had good knowledge (71.9%), 73 people (27.3%) had sufficient knowledge, and 2 (0.7%) had poor knowledge. that there is no relationship between knowledge and attitudes towards behavior while in adolescents. To see the relationship between knowledge and behavior, a statistical test was carried out using chi square, and the p value was obtained = 0.113 (> α = 0.05). So it can be concluded that there is no relationship between knowledge and sedentary behavior at risk of obesity in adolescents in Medan.